Effective reading Reading Skills for Advanced Students - Greenall, Simon (Nxb. Tp. Hồ Chí Minh, 1998)
People and personalities; Food and drink; Houses and safety at home; Jobs and employment; Shopping, consumer affairs, advertising; Travel; Wildlife and the environment; Medicine and physical condition...